Religious Studies of the ideas concerning the posthumous fate of unbaptized infants in the Western Christian tradition - Kuzev, Valery (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The article presents the evolution of ideas concerning  the posthumous fate of unbaptized infants in the Western Christian tradition. According to the Catholic Church doctrine the Limbo of Infants (limbus infantium) is a permanent place/state, providing for an exclusion from the happiness of the beatific vision and intended for those who have died without personal sins, but whose original sin has not been purified by baptism.The first part of the paper presents the reconstruction of formation the concept of limbus infantium. The author refers to the works of Western theologians and religious philosophers who have had the greatest influence on the formation and development of the Limbo of Infants theory (St. Augustine, Peter Abelard, and Aquinas). The teaching about the Limbo was a satisfactory answer to the ethical and theological objections raised against some aspects of the theory of original sin developed according  to the Augustinian tradition. The author shows the role and place of the Limbo theory in Christian soteriology, hamartiology (the dogma of original sin), and eschatology. The Limbo theory held a strong position in the doctrinal complex of Catholicism. Until the second half of XX century the teaching of Limbo was considered one of the elements of the general doctrine of the Catholic Church. In the second part of the paper the author investigates the functioning peculiarities of the Limbo teaching  in the modern era. Modernization, which has affected many aspects of the religious doctrinal statements, resulted in reconsideration of the traditional dogma concerning the afterlife. It is revealed that under the influence of a number of factors contemporary Catholic theology demonstrates a tendency to reject the Limbo theory